A Rare Case of Puerperal Mortality in Ewe: Uterine Tetanus? - Balaganur , krishnappa; Kumar, Davendar; KalyanDe; Sisodia, Shankar Lal (The Indian Journal of Animal Reproduction, 2024)
Study reports a rare case of puerperal ewe suspected for uterine tetanus. The ewe was presented with increased respirationand stiff hind limbs and became recumbent on the tenth day of her lambing. The ewe died despite being treatedsymptomatically, with the discharge of thick creamy pus from external genitalia. Grams-staining of the impressionsmears didn’t reveal the Clostridium tetani organisms.
Keywords: Puerperal; Tetanus; Lockjaw; Sawhorse; Sheep